Social approach to stunting prevention in Blora, Central Java, Indonesia - Muhtar Muhtar; Bambang Pudjianto; Habibullah Habibullah (Universitas Trunojoyo Madura, 2022)
Stunting is a major problem in many developing countries, including Indonesia. The stunting rate in Indonesia is the fifth highest in the world. For this reason, the government is committed to handling it in an integrated manner. The social approach through the assistance of the Family Hope Program (PKH) and the Sembako Program is one of the efforts to reduce stunting. The structural-functional theory in sociology focused on the social order is used as an analytical tool. This research approach is qualitative, and the researchers are the main instrument. Data collection techniques used: interviews, documentation, and observation. The results showed a social approach through the basic food and PKH programs accompanied by continuous assistance to beneficiaries in the form of coaching aspects of health, education, childcare patterns, and the use of social assistance and integrated with other programs contributed to stunting prevention in Blora Regency, Central Java Province. This social reality is in line with the structural-functional theory that society as a system is interrelated or related to other parts of the system.